DEVELOPING PERSONAL COMPETENCY TEST INSTRUMENT IN IDENTIFYING THE ATTITUDE OF RADICALISM - Rahmat Syah; Lusiana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The era of globalization of radicalism develops rapidly, especially through the social networks accessed by high school students and university students. Thus, it is necessary to measure students' radicalism attitudes to know the description of students’ characters so that the institution can take prevention or coaching actions. This study aimed to develop a college entrance test instrument, especially the entrance test at IBM ASMI. The developed instrument was the Personal Characteristics Test (TKP) instrument which could identify radicalism. The research method was R & D development research with qualitative and quantitative approaches. The content of the instrument was validated through the experts judgment and proven by construct validity by conformatory analysis and proven reliability. The results of this study was a valid and reliable measurement instrument that could identify radicalism for students. There were 5 dimensions of radicalism, starting from religion, family, personality, political views, and social relations. Focus Group Discussion produced 5 dimensions, 13 indicators, and 35 items that could be used to measure students’ radicalism attitudes. The results of the validity test contained 2 items that needed to be improved. The results of the reliability of the instruments developed were high and the instrument was ready to use.